Hydrothermal synthesis of 2D MoS2 nanosheets for electrocatalytic hydrogen evolution reaction. Issue 109 (20th October 2015) - Muralikrishna, S.; Manjunath, K.; Samrat, D.; Reddy, Viswanath; Ramakrishnappa, T.; Nagaraju, D. H.
Abstract : Herein, we have designed and synthesized highly electocatalytically active 2D MoS2 nanosheets (NS), by a facile hydrothermal method, for hydrogen evolution reaction (HER). Abstract : Nanostructured molybdenum disulfide (MoS2 ) is a very promising catalyst for producing molecular hydrogen by electrochemical methods. Herein, we have designed and synthesized highly electocatalytically active 2D MoS2 nanosheets (NS) from molybdenum trioxide (MoO3 ) by a facile hydrothermal method and have compared their electrocatalytic activities for hydrogen evolution reaction (HER). The electrochemical characterization was performed using linear sweep voltammetry (LSV) in acidic medium. The MoS2 NS show a HER onset potential at about 80 mV vs. reversible hydrogen electrode (RHE) which is much lower than MoO3 (300 mV). The MoS2 NS and MoO3 show a current density of 25 mA cm −2 and 0.3 mA cm −2, respectively at an overpotential of 280 mV vs. RHE. The MoS2 NS showed an 83 times higher current density when compared to MoO3 . The Tafel slopes of the MoS2 NS and MoO3 were about 90 mV per dec and 110 mV per dec respectively. This suggests that MoS2 NS are a better electrocatalyst when compared to MoO3 and follow the Volmer–Heyrovsky mechanism for HER.